Wider die verhängnisvolle neue Bescheidenheit: Kapitalismus ohne Alternative: Am »Ende der Utopie« gilt: Demokratie und Sozialismus - Narr, Wolf-Dieter; Roth, Roland (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
In critical distance to the "Zeitgeist", the attempt is made to strengthen systematical and topical reasons for the necessity of a socialist alternative. Whoever really wants human rights and democracy, according to the main thesis of the article, cannot ignore socialism.